Self-assembly of a porphyrin derivative on Cu(111) surface under electrochemical control - Thanh Hai Phan; Thi Mien Trung Huynh; Le Tuan Nguyen; Van Hoang Cao; Phi Hung Nguyen; Klaus Wandelt (My University, 2017)
Self-assembly of a porphyrin derivative on Cu(111) surface under electrochemical control
Keywords: Porphyrin derivative; Cu(111) surface; Electrochemical control